Shell and Tube Heat Exchanger Design Using Silica Nanofluid from Lemongrass Leaves - Baariq Fauzaan Andang Paryawan; Asep Bayu Dani Nandiyanto (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
One of the frequently used pieces of equipment in most industrial applications is heat exchanger. The design of a heat exchanger is very effective to reduce total production costs, compared to buying a ready-made exchanger. The purpose of this research is to design a shell and tube type heat exchanger (two passes) using silica nanofluid that produce from bimass lemongrass for nanosilica raw material. TEMA standard is used to obtain the dimensional specifications of the device. Then, these parameters are calculated manually using the Microsoft Excel application to evaluate the performance of the designed heat exchanger. The results of the study indicate that the designed heat exchanger has met the standard. The heat exchanger has 115 tubes with effectiveness around 75%. Although some parameters still do not meet the standards, so further research is needed to meet the permitted standards. A high value of tool effectiveness indicates that the heat exchanger has good performance. In future, we hope this planning and design can be used as a reference in the design of a heat exchanger to be more economical, effective, and has high reliability in the production activity